Biotechnological solutions for improving the quality and environmental friendliness of sugar in the food industry - S. Prystash; O. Pysmennyi; Yu. Zadorogniy (Тваринництво та технології харчових продуктів, 2025)
Sugar production has a significant impact on the environment, which makes it necessary to introduce more efficient and environmentally friendly technologies. One such alternative is the use of biotechnological approaches to improve the quality of sugar syrups and the production of organic sugar without the use of chemicals. The purpose of this study was to evaluate the efficiency of enzymatic methods of syrup purification using pectinesis and amyloglucosidase and determine their impact on the quality of the final product, as well as to investigate the possibilities of processing sugar by-products into useful substrates for other food industries. Enzymatic purification and ultrafiltration methods were used to achieve this goal. During the experiments, a syrup with a residual pectin content of 0.02% ± 0.005 and starch content of no more than 0.01% was obtained, which indicates a high level of purification. The combined use of enzymatic and membrane methods allowed improving the stability of the process and increasing productivity to 120 litres of syrup per hour, which also helped to reduce energy costs by 8% and reduce the duration of technological stages by 10%. The results showed that enzymatic purification of the syrup reduced the level of impurities in molasses and contributed to an increase in the yield of bioethanol to 88% ± 2, which is 9% higher than in the control group. It was found that the feed obtained from pulp after biotechnological treatment had high quality indicators: a decrease in moisture content to 10% ± 0.5, a decrease in microbial activity to 5 × 103 CFU/g and increase the mechanical strength of pellets to 92% ± 4. The results showed significant benefits of enzymatic technologies, in particular, reducing the cost of chemical reagents and waste disposal. The practical significance of the study lies in the fact that the use of biotechnological methods can significantly increase the efficiency of organic sugar and feed production, helping to reduce the environmental burden